Metode Harmonisasi Kewenangan Mengadili Sengketa Pertanahan Yang Terpencar Antara Publik Dan Privat - Dani, Umar (Jurnal Hukum & Pembangunan, 2025)
To obtain the land ownership rights divided into two legal sources, that is private law and public law. The ownership criterion should not be used as the only reference to measure which judicial authority would be competent whether Administrative Courts or Civil Courts. To discover the intersection of judicial authority, it must be based on the source, characteristic, type and touchstone of adjudication. It intends to revised the law and to avoid legal misperception. The aims of this research are, firstly, to understand the differences between land ownership rights dispute in the fields of private law and public law in the other hand. Secondly, to decisive what is the absolute judicial authority of Administrative Courts and Civil Courts. This research uses doctrinal research by prescriptive-analytic type. The research results show that the ownership rights dispute in the field of private law concern the 'validity of the distribution of rights' whereas the ownership rights dispute in the fields of public law concern about the 'validity of the grant of rights'. Decisive the absolute judicial authority is carried out through reconditioning of its functions using the principles of lex specialis derogat lex generalis and oplossing theory. The results show that Land Title Deed is a form of granting rights in the competency of public law. So that the conclude of ownership of rights dispute which object is a land title deed, fully the authority of administrative courts.